v-jun cooperates with v-erbB to transform the thrombocytic/megakaryocytic lineage. - Garcia, M (1993)
The transforming properties of v-jun, the viral counterpart of the transcription factor AP1, were investigated in avian hematopoietic cells. Two retroviruses, called JB and JBN, expressing both v-jun and v-erbB, were constructed using an avian erythroblastosis-based vector. We show that the cooperative action of both oncogenes allowed the virus to efficiently transform bone marrow cells. No such transformation was obtained with either oncogene alone. JB-transformed bone marrow cells expressed GATA-1, TAL-1, and histone H5, suggesting that they belong to the erythrocytic/thrombocytic lineage. (Thrombocytes are the avian homologues of mammal megakaryocytes.) Moreover, after induction with phorbol 12-myristate 13-acetate JB-transformed bone marrow cells began to differentiate and synthesized high levels of platelet glycoproteins, indicating that they were of thrombocytic origin. These results were confirmed by c-ets1 analysis since this transcription factor, specifically found in cells with megakaryocytic but not erythrocytic features, was clearly detected in these cells.